The Rules Of Divorce Before Consummation Of Marriage (Dukhul) - Nazek Salem Muhammad Hanani (My University, 2011)
This research addresses the issue of divorce before consummation of marriage (Dukhul) in Islam and is submitted in completion of the requirements for a Master Degree at the Faculty of Graduate Studies at An-Najah National University. The research is divided into four chapters and a conclusion. In the first chapter, the researcher discussed the definition of divorce in general and mentioned that verses and Hadiths that indicate its legitimacy. She also stated the conditions and requirements that must be available in order for the divorce to take place which include the husband, the wife and the statement of divorce. Furthermore, the researcher mentioned the opinion of Islam regarding the issue of divorce, the types of divorce (Explicit and implicit, Sunni and Bida’ee, revocable divorce, irrevocable divorce. Other types of divorce include the Talaq Munjaz, conditioned divorce and the divorce added to a future time. Then the researcher discussed the rules of divorce in Islam with respect to inheritance for the divorced and how she can return back to her husband. In chapter two the researcher discussed divorce before consummation of marriage (Dukhul) and explained its rules, as well as its effects which include pleasure for the divorced, a dowry, a return back, Iddah, or inheritance for her before consummation of marriage (Dukhul). She also discussed the reasons behind the spread of divorce before consummation of marriage (Dukhul) through the interview she conducted with the judges at the Shari’a courts. The researcher also presented a number of cases that these courts have addressed and gave a number of solutions after detecting the statistics related to divorce and the scale of this problem. In the third chapter, the researcher talked about Al-Khalwa (when the man is with his wife alone) before actual consummation of marriage (Dukhul). She also explained the difference between true Khalwa (In which the couples have nothing to prevent them from having consummation of marriage (Dukhul)) and the untrue Khalwa (in which something is present that prevents total consummation of marriage (Dukhul) between the couples). The researcher explained the impact of true Khalwa on inheritance, the Iddah and the returning back if the woman gets divorced before and after consummation of marriage (Dukhul). She also explained the impact of Khalwa on spreading Hurma and the pleasure of the divorced after the Khalwa, as well as the impact of true Khalwa on the dowry. In the fourth chapter, the researcher discussed the types of separation between the husband and the wife before Dukhul (consummation of marriage (Dukhul)). The separation can occur from the woman’s side through Al-Khulu’ or when she chooses herself when she is authorized to divorce. There is also separation through a decision by the judge due to some defects in one of them or when the husband is incapable of carrying out the responsibilities of marriage. Separation can also take place if there are continuous problems between the husband and the wife or due to the absence or imprisonment of the husband for a given period of time. Moreover, separation can occur before the consummation of the marriage if either the husband or the wife abandons Islam as a religion (apostasy), or when one of them commits a taboo with one of the members of the other side’s family that leads to separation. The researcher finally presented a conclusion in which she stated the most important results along with a number of recommendations, and included the key resources that she used in her research.

الحمد لله حمدا يوافي نعمه, والصلاة و السلام على من لا نبي بعده وبعد: فقد جاء البحث لبيان أحكام الطلاق قبل الدخول, ناقشت في فصله الأول تعريف الطلاق بشكل عام, والآيات والأحاديث الدالة على مشروعيته, و الشروط الواجب توافرها في أطراف عقد الطلاق من مطلق ومطلقة وصيغة, وذكرت حكم الطلاق, ثم ذكرت أنواع الطلاق من صريح وكنائي, أو سني وبدعي, والطلاق الرجعي والبائن بنوعيه بينونة صغرى أو كبرى, ومن أنواع الطلاق أيضا الطلاق المنجز والمعلق على شرط و الطلاق المضاف إلى زمن في المستقبل. ثم تناولت أحكام الطلاق من ميراث للمطلقة, وكيفية رجوع الزوجة المطلقة إلى زوجها. وفي الفصل الثاني تكلمت عن الطلاق قبل الدخول و بينت أحكامه وآثاره من متعة للمطلقة أو مهر أو رجعة أو عدة أو ميراث للمطلقة قبل الدخول. وقد بحثت أسباب انتشار الطلاق قبل الدخول من خلال مقابلات مع بعض القضاة في المحاكم الشرعية, وعرضت بعض القضايا التي تناولتها هذه المحاكم, وبعد رصد إحصائيات الطلاق والوقوف على حجم مشكلة الطلاق قبل الدخول اقترحت بعض الحلول. أما الفصل الثالث فقد تحدثت فيه عن الخلوة قبل الدخول, والفرق بين الخلوة الصحيحة والخلوة الفاسدة, وبينت أثر الخلوة الصحيحة على الميراث و العدة والرجعة إذا طلق قبل الدخول وبعد الخلوة, وأثر الخلوة أيضا على نشر الحرمة ومتعة المطلقة بعد الخلوة, وأثر الخلوة الصحيحة على المهر . وفي الفصل الرابع تحدثت فيه عن أنواع التفريق قبل الدخول, فقد يكون تفريقاً من الزوجة بالخلع أو تختار نفسها إذا فوضت بالطلاق, والتفريق بحكم من القاضي بسبب العيب أو عسر الزوج عن النفقة أو المهر, أو الشقاق بين الزوجين أو بسبب غيبة الزوج و حبسه. وقد يكون التفريق بين الزوجين قبل الدخول بحكم الشرع لردة أحد الزوجين, أو فعل الزوج أو الزوجة بأصول أو فروع الطرف الآخر ما يوجب حرمة المصاهرة. ثم أنهيت البحث بخاتمة بينت فيها النتائج التي خلصت إليها من هذا البحث مع أهم التوصيات. وألحقت الخاتمة بأهم مصادر البحث التي اعتمدت عليها في البحث.
أحكام الطلاق قبل الدخول